2013
DOI: 10.1155/2013/460820
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Pyruvate Prevents Methyglyoxal-Induced Retinal Vascular Injury in Rats

Abstract: Pyruvate is an endogenous antioxidant substance. The aim of this study was to investigate the protective effects of ethyl pyruvate (EP) on retinal vascular injury in diabetic retinopathy. To investigate the protective effect of EP on vascular cell apoptosis and blood-retinal barrier (BRB) breakage, we have used intravitreally methylglyoxal-(MGO-) injected rat eyes. Apoptosis of the retinal vascular cell that was stimulated by the intravitreal injection of MGO was evidently attenuated by the EP treatment. EP ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…VEGF directly decreases the EC tight junction (TJ) content or increases their phosphorylation ( 7 ), either or the two of these effects may enhance paracellular permeability. In support of this, a previous study by our group has demonstrated that methylglyoxal, a potent precursor of AGEs, increased the expression of VEGF in retinal tissues, which elicits retinal vascular hyperpermeability ( 8 ).…”
Section: Introductionsupporting
confidence: 59%
“…VEGF directly decreases the EC tight junction (TJ) content or increases their phosphorylation ( 7 ), either or the two of these effects may enhance paracellular permeability. In support of this, a previous study by our group has demonstrated that methylglyoxal, a potent precursor of AGEs, increased the expression of VEGF in retinal tissues, which elicits retinal vascular hyperpermeability ( 8 ).…”
Section: Introductionsupporting
confidence: 59%
“…Pyruvate showed anti-inflammatory effects in various animal models but was restricted by its low stability in aqueous solutions [ 102 ]. Therefore, EP constitutes a more stable compound than pyruvate and exerts anti-inflammatory and protective effects in ROS-mediated models of ischemia and reperfusion [ 103 , 104 , 105 ], hemorrhagic shock [ 106 ], septic shock [ 107 , 108 ], cecal ligation and perforation [ 109 ], acute renal failure [ 110 , 111 ], pancreatitis [ 112 , 113 , 114 , 115 ], thermal injury [ 116 ], brain injury [ 117 , 118 , 119 , 120 , 121 ], cardiac injury [ 122 , 123 ], retinal damage, and uveitis and cataract [ 124 , 125 , 126 , 127 , 128 , 129 ]. The effects of EP on RAGE were also analyzed in several studies, showing a reduction of RAGE expression upon EP treatment [ 130 , 131 ].…”
Section: Glo-i Ages and Rage In Chronic Liver Injurymentioning
confidence: 99%
“…Such compounds were found to prevent from protein glycation by scavenging MG and, some of them, by activating GLO1. Other molecules discovered to have MG‐scavenging properties include the polysaccharides, prebiotics, chitosan, the anti‐inflammatory molecule ethyl piruvate . From this group of compounds, the isoflavone genistein has been recently suggested to be particularly effective in preventing MG‐induced glycation .…”
Section: The Promise Of New Therapeutic Targetsmentioning
confidence: 99%